Pembersihan Sampah dan Penanaman Kembali Mangrove di Pantai Poka Ambon - Jamal, Endang; Fendjalang, Sophia N M; Pattinasarany, Agapery Y. (Pakis Journal Institute, 2025)
Marine debris in the waters has become a significant environmental issue, threatening the balance and function of coastal and marine ecosystems, including mangrove ecosystems. Poka Beach in the inner Ambon Bay is facing the accumulation of waste from local activities and external currents. To address this issue, the Community Service Program from the Faculty of Fisheries and Marine Sciences at Pattimura University organised a coastal cleanup and mangrove rehabilitation at Poka Beach, involving students, the community, and related institutions. This program aims to raise awareness about the threat of marine debris and the role of mangroves in the sustainability of coastal and marine environments and ecosystems. The Community Service activities include site surveys, coordination with relevant parties, beach clean-up actions, and replanting mangrove seedlings. This activity successfully collected various marine debris accumulated at Poka Beach, such as bottles, food packaging, and household items. Amounting 180 kg of plastic waste was sent to the waste bank for recycling. As many as 150 mangrove seedlings were planted at a distance of 1 meter along the 200-meter stretch of Poka Beach. The sustainability of similar programs through education, conservation, community empowerment, and cross-sector collaboration must be carried out to change community behaviour in proper plastic waste management and create cleaner and healthier coastal and marine environments.